Synthesis, Molecular Docking, Pharmacokinetics, Dft Studies And Evaluation Of Antibacterial And Antioxidant Activities Of Some New Pyrazole Derivatives - Abicho Teshale (ASTU, 2021)
Pyrazole derivatives become a good candidate and potential classes of organic compound to play an important role towards medicinal chemistry. This study was aimed to synthesize some pyrazole derivatives via condensation reaction between substituted acetophenone and phenyl hydrazine. Further phenyl hydrazone derivatives treated with Vilsmeier-reagent (DMF and POCl3), after a complete addition of POCl3 to afford the target compound pyrazole derivatives. In present study, compound 97, 102a and 102b were synthesized with 75%, 84% and 86% yield respectively. The synthesized compounds were purified by recrystallization and characterized by spectroscopic techniques (1H-NMR and 13C-NMR). Furthermore, the synthesized compounds were evaluated for their in vitro antibacterial activity against two Gram-negative bacterial strains (E. coli, and P. aeruginosa) and two Gram-positive bacteria (S. pyogenes and S. aureus) by disk diffusion method. Among synthesized compounds, compound 102a showed modern inhibitory activity against tested bacterial strains with 12.5±0.707- 25±0.707 mm zone of inhibition compared to standard drug Ceftazidime (13.5±0.707- 26.0±1.414 mm) at 100 mg/mL. All the synthesized compounds showed high inhibitory activity against Gram-positive, S. aureus at 100 mg/mL with 15.5±0.707 – 7.50±0.040 mm zone of inhibition. The radical scavenging property of these compound was evaluated using DPPH radical assay and among the synthesized compounds, compound 97 and 102b were showed the strongest activity with IC50 values of 1.90 and 1.805 μg/mL, respectively. While, the IC50 value of ascorbic acid was 1.636 μg/mL. The synthesized compounds were evaluated for their in silico molecular docking analysis using tyrosyl-tRNA synthetase and were found to have minimum binding energy ranging from – 8.0 to –8.4 kcal/mol. Compound 97 and 102a scored better docking efficiency with binding affinity of – 8.3 kcal/mol and – 8.4 kcal/mol respectively. The result of in silico molecular docking study of the synthetic compounds against Human myeloperoxidase was in good agreement with in vitro antibacterial and antioxidant analysis. Compound 102a has shown the best binding score (– 9.3 kcal/mol). The drug likeness of the synthesized compound was performed and satisfies the Lipinski's rule of five with zero violations. The method used here to synthesize the compounds was efficient for the preparation of various pyrazole derivatives of enhanced biological activities in drug discovery program.
Keywords: Pyrazole, Vilsmeier-reagent, Antibacterial, Antioxidant, Molecular docking